Comparison of dried ethanolic extract of Croucus sativus L. and imipramine in the treatment of mild to moderate depression: a double-blind, randomised trial - SH Akhondzadeh; MR Mohammadi; M Khani; AH Jamshidi; A Daliri; SH Bastani (Institue of Medicinal Plants, ACECR, 2003)
Depression which is thought to result from biochemical changes in the brain, is a common disease of adulthood. Persian traditional medicine proposes antidepessant effect for Crocus sativus whereas there is no evidence-based document. Our objective was to compare the efficacy of dried extract of Crocus sativus with imipramine in the treatment of mild to moderate depression in a 6- week double - blind, randomised trial. 30 adult outpatients who met the Diagnosic and Statistical Manual of Mental Disorders, 4th edition for major depression based on the structured clinical interview for DSM IV participated in the trial. Patients have a baseline Hamilton Rating Scale for Depression score of at least 18. In this double-blind, single-center trial, patients were randomly assigned to receive dried extract of Crocus sativus 30 mg/day (capsules) Group (A), imipramine 100 mg/day (capsules) Group (B). In this small preliminary double-blind and randomzed trial, dried extract of Crocus sativus was found to be effective compared to imipramine in the treatment of mild to moderate depression (F=2.91, d.f.=1, P=0.09). In the imipramine group anticholinergic effects such as dry mouth was observed more often that was predictable. The main overall finding from this study and a recent reported animal study is that, dried extract of Crocus sativus may be of therapeutic benefit in the management of mild to moderate depression. A large-scale trial is justified.